2015
DOI: 10.1167/iovs.14-14994
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Among Spectral-Domain Optical Coherence Tomography, Standard Automated Perimetry, and Stereophotography in the Detection of Glaucoma Progression

Abstract: Methods obtained acceptable agreement outcomes in terms of PABAK, AC1, and OPA. However, most cases with detectable changes were identified only by one examination method, resulting in low Ppos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
3
16
0
Order By: Relevance
“…24 In our study, the conventional comparison method, AMAF, and GPA of the VF test could detect glaucoma progression in 20.4%, 45.6%, and 31.1% of the eyes with a mild baseline VF defect (MD4 − 6 dB), respectively. Consistent with a previous study, 23 we also found that stereo photographs detected fewer eyes with glaucoma progression than GPA of the VF test in the early stages of glaucoma, but AMAF could detect progression in more eyes than GPA. These reports are comparable with previous studies using flicker chronoscopy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…24 In our study, the conventional comparison method, AMAF, and GPA of the VF test could detect glaucoma progression in 20.4%, 45.6%, and 31.1% of the eyes with a mild baseline VF defect (MD4 − 6 dB), respectively. Consistent with a previous study, 23 we also found that stereo photographs detected fewer eyes with glaucoma progression than GPA of the VF test in the early stages of glaucoma, but AMAF could detect progression in more eyes than GPA. These reports are comparable with previous studies using flicker chronoscopy.…”
Section: Discussionsupporting
confidence: 92%
“…These reports are comparable with previous studies using flicker chronoscopy. 24 In a previous study, 23 the agreement between stereo photographs and GPA of the VF test was moderate (κ = 0.21), as was the agreement between the AMAF (κ = 0.337) and the conventional method (κ = 0.124) in our study (Table 2). Compared with the conventional comparison method, AMAF improved agreement with the functional test and performance.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…There are also indications that the agreement between visual field progression and progression in optic disc photographs may be better than that between optic disc photographs and automated imaging results. 4 Monoscopic photographs was the method available to us, and is commonly used in clinical practice. While stereoscopic photographs often are regarded as the “gold standard”, stereoscopic classification has not shown any convincing advantage as compared with monoscopic classification in the ability to assess glaucoma likelihood.…”
Section: Discussionmentioning
confidence: 99%
“…There is a wide range of supplementary information in a patient history which may improve glaucoma diagnosis and treatment decisions. However, except for patient age in some cases, the findings of a patient history may not be included in glaucoma studies 9, 10, 11, 12, 13. Some studies may include the use of only family history rather than a full patient history 14, 15, 16.…”
mentioning
confidence: 99%